2009
DOI: 10.1093/europace/eup368
|View full text |Cite
|
Sign up to set email alerts
|

Home orthostatic training in vasovagal syncope modifies autonomic tone: results of a randomized, placebo-controlled pilot study

Abstract: This was the first placebo-controlled study in orthostatic training which has demonstrated that such a study is indeed feasible. An enhancement in overall autonomic tone is observed with HOT in tandem with a non-significant trend in symptom improvement. A larger, adequately powered, randomized controlled trial of tilt-training is now needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 29 publications
1
41
1
3
Order By: Relevance
“…Previous studies have indicated that humoral mechanisms ---the renin---angiotensin system 20 , baroreflex changes, and overall autonomic alterations ---may be involved in the responses observed. 21---24 In particular, Verheyden et al 23 observed increased vasoconstrictor reserve without changes in baroreflex or autonomic tone, while Tan et al 24 showed increases in HF and LF indicators of increased autonomic tone. Our study is the first to relate hemodynamic changes to modifications in autonomic tone assessed by changes in BP and HR variability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that humoral mechanisms ---the renin---angiotensin system 20 , baroreflex changes, and overall autonomic alterations ---may be involved in the responses observed. 21---24 In particular, Verheyden et al 23 observed increased vasoconstrictor reserve without changes in baroreflex or autonomic tone, while Tan et al 24 showed increases in HF and LF indicators of increased autonomic tone. Our study is the first to relate hemodynamic changes to modifications in autonomic tone assessed by changes in BP and HR variability.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] One of the problems in interpreting the results of these trials was that there was low compliance in the group of patients allocated to tilt training. More recently, Tan and colleagues 22 published a blinded study of 22 patients in which the control group performed a sham maneuver, and those patients allocated to tilt training had fewer recurrences than those in the control group.…”
Section: Tilt Trainingmentioning
confidence: 99%
“…Tilt training, involving repeated orthostatic challenge either at home or with tilt table testing has proven helpful in highly motivated patients. In addition to symptomatic benefits, patients who tilt train show improvements in baroreflex sensitivity and heart rate variability compared to those who undergo sham training [55]. Evidence to support pharmacological management in VVS is limited and often conflicting.…”
Section: Vasovagal Syncopementioning
confidence: 99%